2018
DOI: 10.33140/ijnn.03.02.1
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Roughness in Random Superhydrophobic Surfaces

Abstract: To investigate the role of roughness in superhydrophobic coatings a variety of superhydrophobic and non-superhydrophobic surfaces were synthesized using various polymer binders, nanosilica particles and fluoro chemistry on both glass and polycarbonate substrates. The roughness of the coatings was measured by profilometry and atomic force microscopy (AFM) and analyzed by a variety of statistical methods. Superhydrophobic surfaces showed a peak to peak distance below 5 microns and a radius of less than 0.5 micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 36 publications
1
2
0
Order By: Relevance
“…As manifested in Table 5, an Rku >3 was obtained in all systems. As pointed out by Nahum et al [52], skewness and kurtosis are not characteristics for SH, as also shown in this work. Confocal microscopy is generally limited to micro-sized roughness, while scanning electron microscopy allows for the sub-micron analysis of a surface.…”
Section: Parametersupporting
confidence: 77%
See 2 more Smart Citations
“…As manifested in Table 5, an Rku >3 was obtained in all systems. As pointed out by Nahum et al [52], skewness and kurtosis are not characteristics for SH, as also shown in this work. Confocal microscopy is generally limited to micro-sized roughness, while scanning electron microscopy allows for the sub-micron analysis of a surface.…”
Section: Parametersupporting
confidence: 77%
“…Rq is commonly used to characterize surface roughness and is an indication of statistical surface height. A higher Rq value means a rougher surface, while a lower Rq value indicates a smoother surface [16,52,53]. As can be noticed Error!…”
Section: Confocal Morphology Analysismentioning
confidence: 82%
See 1 more Smart Citation